2014
DOI: 10.1016/j.contraception.2013.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of levonorgestrel-releasing intrauterine system (LNG-IUS) 13.5 mg in contraception

Abstract: Background-LNG-IUS 13.5mg (total content) is a low-dose levonorgestrel intrauterine system for up to three years of use. This analysis evaluated the cost-effectiveness of LNG-IUS 13.5mg in comparison with short-acting reversible contraceptive (SARC) methods in a cohort of young women in the US from a third-party payer's perspective.Study Design-A state-transition model consisting of three mutually exclusive health statesinitial method, unintended pregnancy (UP) and subsequent method -was developed. Costeffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…The model made the following assumptions: (1) pregnancy intentions remained stable over the 1-year time horizon; (2) women giving birth would not get pregnant again within 1 year; (3) women who discontinued contraception would not start again, except possibly after a pregnancy that did not result in a live birth 19,20 ; (4) in keeping with a previous cost-effectiveness analysis, women with an ectopic pregnancy were assumed not to be at risk for pregnancy for 2 menstrual cycles 21 ; (5) similarly, after a spontaneous or induced abortion women were assumed not to be at risk for pregnancy for 3 cycles 21 ; (6) effectiveness estimates and probability of discontinuation accounted for contraceptive adherence; (7) side effects of contraception resulted in negligible direct medical costs; and (8) the effectiveness of oral EC decreased as BMI increased. 4 …”
Section: Methodsmentioning
confidence: 99%
“…The model made the following assumptions: (1) pregnancy intentions remained stable over the 1-year time horizon; (2) women giving birth would not get pregnant again within 1 year; (3) women who discontinued contraception would not start again, except possibly after a pregnancy that did not result in a live birth 19,20 ; (4) in keeping with a previous cost-effectiveness analysis, women with an ectopic pregnancy were assumed not to be at risk for pregnancy for 2 menstrual cycles 21 ; (5) similarly, after a spontaneous or induced abortion women were assumed not to be at risk for pregnancy for 3 cycles 21 ; (6) effectiveness estimates and probability of discontinuation accounted for contraceptive adherence; (7) side effects of contraception resulted in negligible direct medical costs; and (8) the effectiveness of oral EC decreased as BMI increased. 4 …”
Section: Methodsmentioning
confidence: 99%
“…A state transition model was developed to assess the total cost and effect of available contraceptive methods in the United States; the methods and results of this model are described in detail elsewhere [9]. The current analysis uses this model to estimate the annual costs associated with available LARC methods [levonorgestrel (LNG)-IUS) 20 mcg/24 h (total content 52 mg), implant and the copper IUD], SARC methods (generic OC, patch, ring and injections), condom and no method as the core contraceptive methods currently used by young women in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…The model structure builds on a previously published study [9] and consists of three mutually exclusive states: (a) initial contraceptive method, (b) UP resulting from contraceptive failure and (c) subsequent contraceptive method. All women began in the initial contraceptive method state.…”
Section: Methodsmentioning
confidence: 99%
“…A study in the USA has suggested that women switching to the LNG-IUS 13.5 mg from a short-acting method may generate cost savings, principally via a decrease in costs associated with unplanned pregnancy expenditure, and that there may also be savings in terms of contraceptive costs in the long term 16. No cost-effectiveness comparisons were identified with Mirena or the potentially cheaper ‘hybrid’ LNG-IUS products that are being introduced for treatment of heavy menstrual bleeding and that might ultimately be licensed for contraception 17…”
Section: Costmentioning
confidence: 99%